Antibacterial Activity of Moringa Plants (Moringa oleifera Lam.) to Overcome Antibiotic Resistance: A Systematic Review - Novitarini; Jason Merari P.; Dian Marlina (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Antibiotic resistance This causes the performance of synthetic antibiotics to decrease, so it is necessary to search for natural antibiotics. Moringa plant (Moringa oleifera Lam.) has antibacterial activity proven to inhibit and kill pathogenic bacteria and Multi-Drug Resistance (MDR)article review aims to collect data related to testing the antibacterial activity of Moringa plants as an effort to overcome antibiotic resistance. The method follows the PRISMA-2020 protocol by searching data on PubMed and ScienceDirect media using the keywords: "Antibacterial activity" and "Moringa oleifera". The data selection uses the Rayyan application by considering the inclusion and exclusion criteria that have been set. The final results obtained are 95 data which are experimental journals of the Randomized Control Trial (RCT) type published in 1981-2021. Moringa plants began to be investigated for their activity against MDR bacteria in 2012 and became a sign that research was already in the direction of finding solutions. Antibacterial testing was carried out in vitro (10 studies) and in vivo (1 study). The leaves have been thoroughly tested for their activity against Methicillin-Resistant Staphylococcus aureus (MRSA). The results of in vitro study obtained the range of zone of inhibition, minimum inhibitory concentration, and minimum kill concentration, respectively: 8.3-12 mm; 0.25-20 mg/ml; 0.50-20 mg/ml study in vivo showed that there was the healing of MRSA infection wounds in test animals.